THE ANALYSIS OF STUDENTS’ MOTIVATION IN ENGLISH ONLINE LEARNING - Mentang, Debora Ireine Karen; Tuna, Jim R.; Liando, Nihta (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2022)
The aim of this research is to find out type of students’ motivation in English Online Learning, whether they had integrative or instrumental motivation. The method used in this research was descriptive quantitative and the technique sampling used in this research was random sampling. The researcher used survey method to analyze the data by distributing questionnaire. The population of this research were 47 students of the grade 8th in SMP N 2 Tondano who have facilities such as handphone and internet quota. The result of the findings of the research showed that type of students’ motivation in English Online Learning that they had was integrative motivation. It was suggested for teacher is expected to grow and maintain students learning motivation to always enjoy, be earnest in learning, and keep improving their language skills.